Knockdown of CENPN Inhibits Glucose Metabolism and Induces G1 Arrest in Esophageal Cancer Cells by Regulating PI3K/AKT Signaling Pathway - Xu, Shasha; Wei, Xing (Hormone and Metabolic Research, 2023)
Esophageal carcinoma (ESCA) is a deadly malignancy with an increasing incidence year by year. The purpose of this study was to explore the function of CENPN in ESCA. Based on TCGA public data platform, the transcription level of CENPN in ESCA was analyzed. Subsequently, ESCA cells with CENPN overexpression or knockdown were constructed. The proliferation and migration levels of ESCA cells were evaluated by CCK-8, colony formation assay, and transwell analysis. Western blotting was used to detect protein levels associated with CyclinD1, CDK2, GLUT1, and PI3K/AKT signaling pathways. Cell cycle distribution was measured by flow cytometry. Glucose consumption and lactate production in ESCA cells were measured. CENPN was overexpressed in ESCA. In vitro experiments showed that CENPN promoted the proliferation and migration of ESCA cells, and upregulated the levels of CyclinD1, CDK2, and GLUT1, promoting the cell cycle process, increasing glucose consumption and lactic acid production. In addition, CENPN overexpression increased the phosphorylation levels of PI3K and AKT. The results suggest that the abnormal expression of CENPN in ESCA may enhance the malignant phenotype of ESCA cells by activating the PI3K/AKT signaling pathway. CENPN is expected to be a new target for ESCA treatment.
Keywords: ESCA; CENPN; PI3K/AKT; cell cycle; glucose metabolism